Land, Death and Dower in the Settler Empire: the Lost Cause of "The Widow's Third" in Nineteenth-Century New Zealand - Macdonald, Charlotte (Victoria University of Wellington Law Review, 2010)
Exploration of dower right or the 'widow's third' in 1840s-70s New Zealand provides an additional perspective on marriage and property history to the better known story of late 19thC married women's property reform. New Zealand practice broadly followed the curtailed dower history of the 1833 Dower Act (England) with further acceleration driven by the desire to rapidly disencumber land title in order to free property in land for easy sale and exchange. Several dower cases are traced, revealing the circumstances of widows in the social and economic fabric of colonial communities. Debates in the settler parliament in the 1870s reveal increasingly divergent set of understandings around land as property, about inheritance and a concern for the situation of women within, but not beyond, marriage.